2011
DOI: 10.31399/asm.cp.itsc2011p0369
|View full text |Cite
|
Sign up to set email alerts
|

Cold Gas Spraying of Ceramics Using the Example of Titanium Dioxide

Abstract: Functional titanium dioxide coatings have a high potential for photocatalytic applications. However, the high process temperatures of conventional thermal spray methods lead to undesirable phase transformations. Cold gas spraying seems to be beneficial, since for ceramic coatings no phase transformations have been observed so far. In this study, bonding of cold-sprayed ceramic particles on metal substrates is elucidated by investigating single impacts obtained from wipe tests. Different feedstock powders were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The result seems to be in agreement with the chemical bonding mechanism. However, the result contradicted that of Gutzmann's, whose experiment showed that preheating the substrates was good for TiO 2 particles deposition [20]. Above all, the bonding mechanism of cold sprayed TiO 2 coatings is still unclear, and a lot of work is needed to clarify it.…”
Section: The Proposed Bonding Mechanismmentioning
confidence: 87%
See 1 more Smart Citation
“…The result seems to be in agreement with the chemical bonding mechanism. However, the result contradicted that of Gutzmann's, whose experiment showed that preheating the substrates was good for TiO 2 particles deposition [20]. Above all, the bonding mechanism of cold sprayed TiO 2 coatings is still unclear, and a lot of work is needed to clarify it.…”
Section: The Proposed Bonding Mechanismmentioning
confidence: 87%
“…It was supposed that the adhesion was caused by the substrates' shear instability, and the jet from substrates would adhere ceramic particles. Gutzmann [20] etc obtained the impact morphology of single TiO 2 and studied the deposition of different particles on substrates with different temperature. It showed that there were concentric rings on the impacted substrates, like the shear instability zone.…”
Section: The Proposed Bonding Mechanismmentioning
confidence: 99%
“…gravity or centrifugal forces, for the separation of particles in homogeneous powders, solids or melts. These methods include the centrifugal casting [16][17][18], slip casting with sedimentation [19], centrifugal powder molding and many others [10]. The disadvantage of almost all methods is the fact that the targeted grading of the reinforcing particles in a component can only be achieved with a high process complexity.…”
Section: Introductionmentioning
confidence: 99%